IMPLEMENTASI PROGRAM ATENSI SOSIAL BAGI PENYANDANG DISABILITAS DI KOTA SUKABUMI - Maharani, Sania; Purwanti, Dian; FY Basori, Yana Fajar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Prof Dr Hazairin, SH, 2023)
In an effort to realize services for the community to provide respect, protection, and fulfillment of the rights of habilitation and social rehabilitation for people with disabilities, the Ministry of Social Affairs of the Republic of Indonesia runs a Social Rehabilitation Assistance service program or known as social ATENSI. Social attention for persons with disabilities is a social rehabilitation service that is carried out on a family basis, LKS/community basis, and on a residential basis. The purpose of this research is to find out how the social attention program is implemented for persons with disabilities in Sukabumi City. The research method used is qualitative with a descriptive approach. The theory used in this study is the theory of policy implementation from O. Jones which has three dimensions including organization, interpretation, and application. Based on the findings from this study, it can be concluded that the implementation of the social attention program for persons with disabilities in Sukabumi City is not optimal so that socialization and data collection of persons with disabilities is needed more broadly because there are still persons with disabilities who have not received social attention assistance.